2017
DOI: 10.1038/s41467-017-00046-0
|View full text |Cite
|
Sign up to set email alerts
|

Inherited determinants of early recurrent somatic mutations in prostate cancer

Abstract: Prostate cancer is a highly heritable molecularly and clinically heterogeneous disease. To discover germline events involved in prostate cancer predisposition, we develop a computational approach to nominate heritable facilitators of somatic genomic events in the context of the androgen receptor signaling. Here, we use a ranking score and benign prostate transcriptomes to identify a non-coding polymorphic regulatory element at 7p14.3 that associates with DNA repair and hormone-regulated transcript levels and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
(69 reference statements)
1
23
0
Order By: Relevance
“…However, no significant association between SPOP mutations with ethnicity, clinical, or pathologic parameters was observed. Interestingly, Romanel et al identified a non-coding polymorphic allele at 7p14.3, associated with SPOP mutations through a hormone dependent DNA damage response [ 200 ]. This genetic predisposition may positively select for SPOP mutations in response to DNA damage.…”
Section: Genomic Landscape Of Advanced and Metastatic Castrate Resmentioning
confidence: 99%
“…However, no significant association between SPOP mutations with ethnicity, clinical, or pathologic parameters was observed. Interestingly, Romanel et al identified a non-coding polymorphic allele at 7p14.3, associated with SPOP mutations through a hormone dependent DNA damage response [ 200 ]. This genetic predisposition may positively select for SPOP mutations in response to DNA damage.…”
Section: Genomic Landscape Of Advanced and Metastatic Castrate Resmentioning
confidence: 99%
“…More recent work has also suggested a genetic predisposition to this distinct subclass of PCA and this may be modulated by AR signaling and DNA repair alterations. 94…”
Section: Insights Into Genomic Complexitymentioning
confidence: 99%
“…AR enhancer duplication [18,33,34] and RB1 exon 7-17 tandem duplication [106] leading to AR overexpression and RB1 protein loss respectively are relevant examples of events discovered through whole genome sequencing studies. Similarly, SNPs located in noncoding inter-or intragenic regions were shown to be associated with specific subtypes of prostate cancer and with disease aggressiveness [107][108][109][110] .…”
Section: Resultsmentioning
confidence: 99%